Identifying Malay regional character through aristocratic architectural elements - Raja Abdul Kadir, Tengku Anis Qarihah; Jahn Kassim, Puteri Shireen; Abdul Latip, Nurul Syala; Abdul Majid, Noor Hanita (UMK Press, 2018)
Malay architectural traditions range from the traditional timber traditions of the early era of the Malay world to the late hybrid forms of the 1800s and early 1900s. The paper attempts to create regional grouping in the Malay world that can be used to characterise the extreme variation and diversity of the aristocratic forms of the Malay world, including hybrid structures, which are Malay modern yet ‘Classical’ forms of architecture which represent potentials for an urban language for the Malay region, and its nations. Any effort to develop a new language must take into account the relative shared character and rules of design that reflect the stylistic character of each region. The paper attempts to trace these stylistic characteristics and rules, in palaces and aristocrat’s buildings, yet it remains observant that Malay architectural language had not been able to withstand the tumultuous changes due to the advent of new materials and technology such as steel and concrete. The origins of the Malay architectural style and language are ultimately linked to the beginnings of the culture and aesthetic forms of the timber-based vernacular style. Due to the rising urbanisation, many of the imported styles are perhaps the core problem of the unsustainability of the present cities and buildings. The research shared and attempts to highlight and identify the set of stylistic character, design principles and building elements of Malay architecture derived from the essences of traditional form and frontage language seen through the diversity of regional styles that can be used in future modern architecture.